Comparison of appointment scheduling perspectives between cost minimization and service level constraint - Wong, Kai Qin (Nanyang Technological University, 2021)
Queueing systems attracted considerable attention from researchers due to its wide application in most industries, such as healthcare. They addressed the issue of scheduling appointments using many different approaches, with the popular one being minimizing the system cost. In this paper, we analyse two different papers with different modelling perspectives, one optimizing the schedule through imposing a service level constraint, while the other through cost minimization. We observe that though the second approach incurs lower costs given all other things equal, customers’ waiting experiences are compromised. On the other hand, the first approach allows more customers to be scheduled within a fixed time frame such that the waiting times of customers do not exceed a given threshold.